New developments in adsorption/separation of small molecules by zeolites - Valencia, Susana; Rey, Fernando (Springer, 2020)
Small Gas Adsorption and Separation in Small-Pore Zeolites -- Critical Overview of Textural Characterization of Zeolites by Gas Adsorption -- Computational approaches to zeolite based adsorption processes -- Efficient downstream processing of renewable alcohols using zeolite adsorbents -- Measurement of Diffusion in Small pore Zeolites to Improve Selectivity in Separation Processes -- Perspectives of scaling-up the use of zeolites for selective separations from lab to industry -- Industrial zeolite applications for gas adsorption and separation processes
Keywords: Inorganic chemistry; Chemical engineering; Environmental chemistry; Analytical chemistry